The Training Needs of the Principles of Educational Training Centers in Riyadh in the Light of Knowledge Trends - Al Faleh, Mashail Bent Nasser (Journal of Educational and Psychological Sciences, 2018)
Subject of the study: The Training Needs of the Principles of Educational Training Centers in Riyadh in the Light of Knowledge Trends. Study Method and tools: The descriptive approach was used , the tools of the study is the questionnaire. Study population-Sample: All trainers (principles – supervisors) in educational training centers in Riyadh , which consisting of (9) principles and (48) supervisors. Questionnaires were distributed to them all , (54) out of (57) responded from the principles and the training supervisors. Results of the Study: 1.The major training needs which got the highest approval rate in the knowledge-producing area are: the ability to produce knowledge in the educational training center, and the ability to encourage the trainees to think, and resolve the problems. 2.the major training needs which got the highest approval rate in the area of knowledge-spreading are: the ability to transform ideas to specific plans, to achieve the training objectives. 3.the major training needs which got the highest approval rate in the area of knowledge-using are: the ability to simplify knowledge based on the trainer’s needs , improve the communication skills. 4.The study indicates that there is no statically differences among the responses of the study sample toward the training needs of the principles of training educational centers attributed to the variables of study (experience , job title , and qualification). Recommendations of the study: -The need of maintain a high degree of democratic and let the principles participate in identifying the training needs. -Evaluating the outcomes of training programs. -Linking the educational training centers in Riyadh with electronic system to facilitate sharing knowledge.